Differential gene expression profiling of metalloproteinases and their inhibitors: a comparison between bovine intervertebral disc nucleus pulposus cells and articular chondrocytes. - Cui, Y; Yu, J; Urban, J; Young, D (2010)
STUDY DESIGN: A comparative in vitro metalloproteinases and their inhibitors gene expression profile. OBJECTIVE: To obtain a complete expression profile of matrix metalloproteinases (MMPs), family of proteases with a disintegrin and metalloproteinase domain with thrombospondin motifs (ADAMTS), and tissue inhibitors of metalloproteinases (TIMPs) in bovine adult nucleus pulposus (NP) cells and to compare this profile with the expression profile obtained from bovine adult articular chondrocytes cultured under identical conditions. SUMMARY OF BACKGROUND DATA: The cells of the NP resemble articular chondrocytes morphologically but produce a matrix which, though consisting of similar components, has very different biomechanical properties. No specific markers for NP cells have yet been identified; they can be distinguished from chondrocytes only by differences in gene expression. Here we compare profiles of gene expression of metalloproteinases and their inhibitors between NP cells and chondrocytes to improve understanding of the differences between these cell types. METHODS: NP cells and articular chondrocytes were harvested respectively from bovine caudal discs and the articular cartilage of metacarpal-phalangeal joints of 18- to 24-month-old steers. These cells were cultured under identical conditions for 96 hours in alginate beads. Expression levels of MMPs, ADAMTSs, and TIMPs were detected by real-time RT-PCR. RESULTS: Gene profiling demonstrated distinct differences between levels of MMPs, ADAMTSs, and TIMPs produced by chondrocytes and NP cells. In particular, NP cells expressed considerably more MMP-2 and MMP-14 than chondrocytes, and expression of ADAMTS-1,-2,-17 and TIMP-1 was also higher. However, expression of MMP-1,-3,-7,-8,-10,-11,-13,-16,-19,-20,-21,-23,-24,-28, ADAMTS-4,-5,-6,-14,-18,-19, and TIMP-3 was lower in NP cells than in chondrocytes. Chondrocytes but not NP cells expressed MMP12 and MMP27; this difference is a potential marker for distinguishing between NP cells and chondrocytes. CONCLUSION: Because culture conditions and animal age were identical, differences in metalloproteinase and inhibitor expression between NP cells and chondrocytes were intrinsic to cell phenotype and not induced by differences in the in situ extracellular environment.